The Relationship between Work-Related Musculoskeletal Disorders and Types of Used Treatment Methods Among Iranian Physiotherapists - Mahdi Rahmati-Yami; Elham Azarmi; Leila Rahnama; Samaneh Hosseinzadeh; Noureddin Karimi (University of Social Welfare and Rehabilitation Sciences, 2020)
Objective: After respiratory disorders, musculoskeletal disorders are the second prevalent cause of short-term sickness absence (less than 2 weeks). The nature of the work in physiotherapy requires physical activities, which include repetitive skills, manual techniques, putting direct pressure on a particular joint, unskilled posture during special maneuvers, and having long postural positions. Several studies have reported that physiotherapists frequently experience musculoskeletal disorders. This study aims to determine the relationship between Work-Related Musculoskeletal Disorders (WRMDs) and the common therapeutic methods used by Iranian physiotherapists. Materials & Methods: This is a descriptive-analytical epidemiological study with a cross-sectional design. The study population consists of physiotherapists working in Iran. Data collection tools included a demographic form, as well as general Nordic questionnaire designed by Kuorinka et al. to detect the WRMD symptoms in 9 body areas in the past year. The questionnaires were distributed among participants in cooperation with the Iranian Physiotherapy Association during the 27th Iranian Physiotherapy Congress. Data analysis was performed in SPSS using the Chi-square and Fisher exact tests. Results: Of 1200 questionnaires distributed among physiotherapists, 685 questionnaires were returned after completion. Of these, 16 were excluded due to missing some inclusion criteria, 4 due to having a work experience less than one year, and 11 due to having other diseases, such as neurological and rheumatic diseases, malignancies, and joint replacement. The mean±SD age of the participants was 37.9±9.91 years ranged from 22 to 69 years; 53.9% of them were female and 46.1% male. After obtaining the prevalence of WRMDs, its significant association with the type of used treatment method was examined by the Fischer exact test. The results showed a significant correlation of WRMDs with treatment methods in 7 out of 9 areas. In particular, WRMDs were associated with manual massage (P=0.001), myofascial release (P=0.011), mobilization (P=0.007), muscle energy technique (P=0.007), and dry needling (P=0.032) in the neck area; with mobilization (P=0.005) and taping (P=0.014) in the shoulder area. Also, WRMDS are associated with respiratory physiotherapy (P=0.007) in elbows. WRMDS are correlated with manual massage (P=0.027), myofascial release (P=0.001), mobilization (P=0.046), muscle energy technique (P=0.004), and taping (P=0.016) in wrists/hands. In the upper back, WRMDs are associated with manual massage (P=0.007), mobilization (P=0.014), and taping (P=0.004). In the lower back, WRMDs are seen with myofascial release (P=0.036), mobilization (P=0.015), taping (P=0.035), and muscle energy technique (P=0.044). Finally, WRDMs are observed with water therapy (P=0.037) in knees. Conclusion: There is a high prevalence of WRMDs among physiotherapists in Iran. Its rate has a significant relationship with the type of treatment methods. Some physiotherapy methods can increase the prevalence of WRMDs.